Hubungan Sales Growth dan Nilai Perusahaan serta Profitabilitas sebagai Variabel Intervening - Cici Widya Prasetyandari (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2021)
The main goal of a company is to maximize company value, this can be used as a benchmark for the company. Company value can be interpreted as the welfare and prosperity felt by shareholders. This study aims to see the effect of growth (Growth Sales) on firm value through profitability as an intervening variable. The method used in this research is a literature study, which analyzes based on books and previous studies that discuss similar concepts. The results of this study are sales growth has an effect on the firm value both through profitability and without profitability. Keywords; Sales Growth, Profitability, Company Value